Predictors of time to recovery from uncomplicated severe acute malnutrition among children in eastern Ethiopia - Yadeta, Shibiru Kelbessa; Tadesse, Trhas; Negese, Tarekegn; Haile, Bisrat; Kebede, Aweke; Motuma, Aboma; Abdurahman, Dureti; Oumer, Abdu; Roba, Kedir Teji (Frontiers in Nutrition, 2024)
Background: Managing severe acute malnutrition (SAM) involves an Outpatient Therapeutic Program (OTP), targeting more than 80% of SAM children where the quality of primary health care remains poor. Treatment success and recovery from SAM remain poor and could be affected by many factors, where such evidence is limited in East Harerghe. This study assessed the predictors of time-to-recovery from SAM in eastern Ethiopia. Methods: A retrospective cohort study was done on 402 records of SAM children under five years of age enrolled on OTP at 12 health posts retrieved from 2020–2021. We used the Kaplan-Meir estimate along with p of log rank test and the survival curve to compare the time to recovery across categories. A multivariable Cox proportional hazard model was fitted to identify predictors of time-to-recovery from SAM. A p-value below 0.05 was used to declare statistical significance. Results: A total of 402 records were reviewed, and the cure rate from SAM was 89.6% (95% Confidence Interval(CI), 87–93). Moreover, a death rate of 0.7%, a default rate of 9.5%, and a non-responder rate of 0.2% were obtained with a median length of stay of 7 weeks. The median time-to-recovery was significantly shorter for children from shorter distances from OTP sites with edema, amoxicillin, and diarrhea (p < 0.05). Edema at admission (Adjusted Hazard Ratio (AHR) = 1.74; 95% CI: 1.33-2.29), without diarrhea (AHR = 1.51; 95% CI: 1.18-1.94), taking amoxicillin (AHR = 1.55; 95% CI: 1.19-2.02), shorter travel time to the OTP site (AHR = 1.44; 95% CI: 1.13-1.85), breastfeeding (AHR = 1.60; 95% CI: 1.27-2.02), adequacy of Ready to Use Therapeutic Food (RUTF) (AHR = 1.22; 95% CI: 0.90-1.65), and new admission (AHR = 1.62; 95% CI: 0.84-3.10) were important predictors of recovery from SAM. Conclusions: Recovery from SAM was found to be acceptable in comparison to the sphere standard and is predicted by edema, diarrhea, distance from the OTP site, amoxicillin, and RUTF adequacy. These allow for focused interventions that address the identified factors for better recovery from SAM.